Competitive Evaluation of Implmenting a Technology Platform Strategy: Thomson Reuters - Jupp, Stephen A (2011)
Following the acquisition of the Financial News and Data company Reuters by Thomson Financials, the industry structure was transformed into a duopoly with Bloomberg and the new Thomson Reuters in head to head competition. During the last three years of economic turmoil, the financial industry has gone through a series of major shake ups and imposed regulations. The rationalization of market data subscriptions and consolidation within the industry has caused Financial Institutes to look long and hard at which suppliers of financial information and market data they valued the most. Reuters has traditionally not fared well in the face of product comparisons with Bloomberg. Additionally numerous trends and developments in the technology environment has seen a proliferation in internet ready mobile devices such as iPAD’s, Blackberry’s and iPhones enabling more flexible and independent means of working. Social trends on social networking, collaboration and community participation has also been brought to the forefront of attention. Video has also become a medium of targeted information delivery in its own right.